Being in the Hyper City, and the Posthuman Body - Davide Landi (Footprint)
Since ancient times, the analogy of the body in relation to buildings was central both in Western and Eastern architectural and urban design. Over time, the prevalence of economies over inhabitants’ experience led to the adoption of architectural and urban strategies to improve spatial efficiency and specialisation. The analogy of body-buildings was affected negatively. Nonetheless, the 21st-century technological revolution transformed the city and its inhabitants into something different. These are quantified cities which are experienced dynamically by quantified post-human beings. Consequently, a renewed paradigm body - built environment is established. Taking this position into consideration, this article critically investigates the paradigm Hyper City – Post-Human body. In this, the article introduces an alternative psychological interpretation of the analogy body - buildings. It is built around an acknowledgement of a necessary continuity between digital and physical domains to effectively question the notion of urbanisation.